Novel Endocuff-assisted Colonoscopy Significantly Increases the Polyp Detection Rate. Issue 5 (May 2015) - Biecker, Erwin; Floer, Martin; Heinecke, Achim; Ströbel, Philipp; Böhme, Rita; Schepke, Michael; Meister, Tobias
<x xml:space="preserve">Abstract</x> Goals and Background: Screening colonoscopy for colorectal cancer has proven to reduce mortality rates. Recently the Endocuff (EC), an attachment to the distal tip of the colonoscope, was introduced. The aim of our study was to compare EC-assisted colonoscopies with standard colonoscopies for the detection of colonic polyps. Study: This study is a randomized prospective 2-center trial. The study was conducted at 2 tertiary care centers. Participants: A total of 498 patients [249 males; median age 67 y; interquartile range (IQR), 56-75 y] for colon adenoma screening purposes were included. All patients underwent standard colonoscopy with or without the use of EC. Overall polyp detection rate, the number of colonic polyps, and the polyp distribution in the colon were measured. Difference in recognition of polyps with or without the use of EC was assessed. Statistical analysis was applied. Results: In the EC group, the number of polyps detected per patient was 63% higher [2.00 (IQR, 1.00-4.00) vs. 1.00 (IQR, 1.00-2.25), P<0.0001]. The polyp detection rate in patients increased by 14% with the use of EC (56% vs. 42%, P=0.001). For polyp detection, superiority by use of EC could be observed in the sigmoid (P=0.001) and cecum (P=0.002) for polyps <1 cm in diameter. In the EC group, the number of adenomas detected per patient significantly increased by 86% (P=0.002). No major complications occurred in both groups. Conclusions: The use of the EC is feasible and safe with significantly higher polyp detection rates, especially for those located in the sigmoid region. The cuff system has the potential to improve the accuracy of screening colonoscopies.